Level of effectiveness of women's capacity development program in generating participants' income - Zaimah, R; Sarmila, M.S; Suhana Saad; Patricia Joseph Kimong (Human Resource Management Academic Research Society (HRMARS), 2025)
A range of capacity development initiatives for women has been executed in Malaysia. The initiatives are executed by a multitude of entities under various designations, yet their overarching aim remains consistent: to enhance women's income generation. This study primarily investigates the effectiveness of the women's capacity development program executed by the Women's Development Department (JPW) in enhancing women's income generation. The aim of this study is to assess the effectiveness of the women's capacity development program in generating income for its participants. This study employed a survey method utilizing a questionnaire. The participants in the study comprised women engaged in the women's capacity development program executed by JPW. The data collection employed a sampling technique, resulting in a total of 261 program participants serving as respondents for the study. The overall results of the study were elucidated through descriptive analysis. The program's effectiveness was assessed through a Likert scale, with the resultant levels of effectiveness classified into categories of low, medium, and high based on average scores. The findings of the study indicated that the program's effectiveness was notably elevated. On average, participants expressed a high level of satisfaction with the benefits derived from the program they engaged in. The findings of the study indicate that these programs may be sustained with enhancements in input over time.